The Relationship Between Work Engagement and Job Performance: Psychological Capital as a Moderating Factor - Yao, Jin; Qiu, Xiangbin; Yang, Liping; Han, Xiaoxia; Li, Yiying (Frontiers in Psychology, 2022)
Based on the job demands-resources model, this study explored the relationships of work engagement, job performance and psychological capital in industry employees. A total of 399 IT programmers were recruited and completed the work engagement scale, knowledge employee job performance scale and psychological capital questionnaire. The results showed that: (1) There is a relationship between work engagement and job performance, which may not be linear but inverted U-shaped, and (2) psychological capital plays a moderating role in the inverted U-shaped relationship between work engagement and job performance.